Peran Lembaga Amil Zakat dalam Menopang Perekonomian Masyarakat Terdampak Covid-19: (Studi Kasus Di Dompet Dhuafa Unit Madiun Tahun 2020) - Mustofa, Baharudin (Fakultas Syari'ah Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo., 2021)
The Amil Zakat Institution is a zakat management organization that is fully formed by the community and confirmed by the government. LAZ is an institution formed by the community which has the task of assisting the collection, distribution, and utilization of zakat. The research method used to discuss the role of the Amil Zakat Institution in Supporting the Economy of Communities Affected by COVID-19 is a qualitative research method. From the research, it was concluded that the economy of the people of East Java after the COVID-19 pandemic experienced a decline, due to loss, vacuum, and the limited activities and livelihoods of the community due to the pandemic where there were restrictions on all community activities which ultimately also affected the community's economy. The projection of the East Java DD program in helping support the community's economy is to increase the realization of ZIS fund collection through programs, online promotions, MPZ partnerships, so that they can bring more benefits to the community, increase public awareness to share, channel ZIS funds through LAZ so that effective distribution, and increasing the human resources of managers and partners of DD Jatim for the creation of professional and maximum ZIS fund management